2010
DOI: 10.1016/j.jip.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Primary hemocyte culture of Penaeus monodon as an in vitro model for white spot syndrome virus titration, viral and immune related gene expression and cytotoxicity assays

Abstract: Immortal cell lines have not yet been reported from Penaeus monodon, which delimits the prospects of investigating the associated viral pathogens especially white spot syndrome virus (WSSV). In this context, a method of developing primary hemocyte culture from this crustacean has been standardized by employing modified double strength Leibovitz-15 (L-15) growth medium supplemented with 2% glucose, MEM vitamins (1×), tryptose phosphate broth (2.95 gl⁻¹), 20% FBS, N-phenylthiourea (0.2 mM), 0.06 μg ml⁻¹ chloramp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 64 publications
0
46
0
Order By: Relevance
“…The lack of success in spontaneous and induced cell line development subsequently paved the way for the attempts on developing fusion cell line [15,16], but, with little success. More recently, researchers have succeeded in viral gene expression [42], determinations of cytotoxicity and genotoxicity [41,43], and viral multiplication [26] employing primary cell culture systems developed from different species of penaeids.…”
Section: History Of Shrimp Cell Culturementioning
confidence: 99%
See 3 more Smart Citations
“…The lack of success in spontaneous and induced cell line development subsequently paved the way for the attempts on developing fusion cell line [15,16], but, with little success. More recently, researchers have succeeded in viral gene expression [42], determinations of cytotoxicity and genotoxicity [41,43], and viral multiplication [26] employing primary cell culture systems developed from different species of penaeids.…”
Section: History Of Shrimp Cell Culturementioning
confidence: 99%
“…To adjust osmolality, NaCl at a concentration ranging from 6 to 12 g/l [9,19,40,49] has also been added besides the balanced salt solutions [40,78]. Addition of vitamins [41,42], proline [49,56,57,82] and glutamine [28,82] has been proven to be the choice of supplements in the growth media. In addition, lactalbumin hydrolizate at a concentration of 0.1-1 g/l [2-4, 39, 48, 55-57], tryptose phosphate broth at 2.95 mg/ml [41,42] and TC Yeastolate at 1 g/l [56,57] have also been used as the source of peptides, amino acids and carbohydrates.…”
Section: Organic and Inorganic Supplements To Improve Growth Of Shrimmentioning
confidence: 99%
See 2 more Smart Citations
“…Well before that Braasch et al (1999) and Jose et al (2010) had reported haemocyte cultures from P. vannamei and P. monodon BrdU positive (1-2 and 22 ± 7 % respectively). Maeda et al (2003) confirmed 35 % BrdU positive cells in primary ovarian cell culture developed from Penaeus japonicus.…”
Section: Discussionmentioning
confidence: 91%